Pengabut Semprot Bergerak untuk Pemberantasan Hama Kelapa Sawit - Pramuhadi, Gatot; Ayu, Zavira Mega; Kusdian, Muhammad Haikal; Fahri, Riza; Pratama, Raesa Firdiansyah; Rahayu, Anik (Jurnal Ilmu Pertanian Indonesia, 2022)
Palm oil (Elaeis guineensis) is a tropical plant that can be attacked by various pests, start from nurseries to plantations, so it is necessary to eradicate pests. Generally, the pests is eradicated by applying pesticides using fogging machines brought down by farmers so that they are ineffective in reaching high plants, and hot smoke from fogging machines can damage oil palm leaves. This study aims to design a tool that can optimize the application of pesticide fog to oil palm plants at a certain height. The tool’s design in the form of a mobile spray fogger also aims to facilitate the operator in applying pesticide fog at various heights of oil palm and, simultaneously, can reduce the impact of damage to oil palm leaves. The research method was carried out by testing the performance of pesticide fog spraying in the laboratory and the performance test of applying pesticide fog using mobile spray foggers on the land. Furthermore, pesticide smoke from fogging machines was optimized by combining electric sprayers and air blowers so that pesticide fog is formed, reducing the temperature of pesticide smoke, and increasing the range of fogging. The performance of the combination of outputs from fogging machines, electric sprayers, and air blowers on mobile spray fogger produces a droplet diameter of 94.41 μm, droplet density of 365.44 droplet/cm2, effective fogging range of 8.63 m, effective fogging width of 0.91 m, and an average temperature decrease of 4°C. Keywords: air blower, electric sprayer, fogging machine, palm oil, pests